The Influence and Importance of Getting Used to English For Elementary School Students Since Grade 1 - Ginting, Herdika Fauzan; Siregar, Syarifah Aini; Putri, Cahya Dwi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
English lessons can officially be taught in Elementary Schools since the 1994 school year as a local content subject. Although in reality there are several schools that have programmed English lessons for their students who are in Study Groups and Kindergarten, or called Early Childhood Education. In this era of information and globalization, the government realizes the importance of the role of English and human resources who have the ability to communicate in English, which in Indonesia is a foreign language. As a forward-looking policy, the government has issued the Constitution of the Republic of Indonesia Number 2 of 1987 concerning the National Education System followed by Government Regulation Number 28 of 1990 which states about human resource development. English lessons need to be implemented early on, because with early English learning, children find it easier to develop English when they become teenagers, namely when children enter Elementary School, Junior High School or to a higher level, the English taught by the teacher will stick in their memory and it is difficult to forget it, compared to children who are not taught English when they are in kindergarten or PAUD. This study aims to obtain a deep and comprehensive understanding of the English language learning process for students.